Integration of heterogeneous system information in machining-detection logistics for titanium alloy blade with adaptive belt grinding. Issue 9 (2nd September 2019) - Xiao, Guijian; He, Yi; Huang, Yun; Liu, Ying; Dai, Wentao; Quan, Li
ABSTRACT: As a key part of an aircraft engine, the profile accuracy and surface quality of the titanium alloy bladesignificantly influence engine usability. Belt grinding is one of the most effective ways to increase thesurface integrity of blades. However, several issues, includingthe elastic contact, change in shape owing to weak rigidity and so on, make it difficult to ensure satisfactory profile accuracy and surface quality.Self-adaptive manufacturing with machining-detection logistics has been reported as a means forsolving these problems. However, as there are different system network architectures and communication protocols in the equipment, sharing information and interoperation isimpossible, integrating these systems is difficult. This study researches the information integration process of three heterogeneous systems, namely 840D, 828D, and Win3Ds, and reportson the concept of homogenising these heterogeneous systems in the network structure based on theindustrial Ethernet network platform using the object linking and embedding for process control (OPC)technology to unify their communication interfaces. Moreover, a self-adaptive belt grinding experimentfor a titanium alloy blade is conducted with a heterogeneous system based on this method. The resultsdemonstrate that this method can achieve information integration in the heterogeneous system of self-adaptive beltgrinding.